how solve this question:-
Attachments:
![](https://hi-static.z-dn.net/files/d34/a1a3ffe82ad78464a6a7122712723b5f.jpg)
Answers
Answered by
0
(2y-3)/4-(3y-5)/2=y+3/4
(2y-3-6y+10)/4=y+3/4
(7-4y)/4=y+3/4
(7/4)-(3/4)=y+y
1=2y
y=1/2
Checking by putting value of y in given equation
LHS
(2*1/2-3)/4-(3*1/2-5)/2
=(1-3)/4-(-7)/4
=-1/2+7/4
=5/4
RHS
=1/2+3/4
=5/4
LHS =RHS
Hence proved
Hope it helps
If yes please mark brainliest
(2y-3-6y+10)/4=y+3/4
(7-4y)/4=y+3/4
(7/4)-(3/4)=y+y
1=2y
y=1/2
Checking by putting value of y in given equation
LHS
(2*1/2-3)/4-(3*1/2-5)/2
=(1-3)/4-(-7)/4
=-1/2+7/4
=5/4
RHS
=1/2+3/4
=5/4
LHS =RHS
Hence proved
Hope it helps
If yes please mark brainliest
Answered by
1
Answer:
Hope it helps you
Pls mark me as Brainliest
Attachments:
![](https://hi-static.z-dn.net/files/dfe/d1ef047e169f8eeca193e6dbbcc73890.jpg)
Similar questions